Association of neutrophil / lymphocyte ratio, platelet / lymphocyte ratio and brachial retinal vein occlusion (Annals of Medical Research, 2021)
Aim: In this study, we aimed to measure neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) levels in brachial retinal vein occlusion (BRVO) patients and to determine whether there it could be used as a marker for BRVO. Brachial retinal vein occlusion is a serious disease that causes vision loss and is associated with inflammation.Material and Methods:This retrospective study included 77 patients with BRVO and 69 healthy controls. BRVO was diagnosed with ophthalmic examination. Blood samples were obtained from venous blood and serum neutrophil, lymphocyte, and platelet data of all patients were recorded also, NLR-PLR values were calculated. Results:Significant difference were not found between the BRVO group and control group with the level of white blood cells (WBC) and platelets (p>0.05). Neutrophil count was significantly increased in BRVOs compared to the controls (4.79±1.89 vs 4.02±1.47, p=0.007). Lymphocyte count was significantly decreased in BRVOs compared to the controls. (2.17±0.76 vs 2.52±1.03, p=0.022) NLR was significantly increased in BRVOs compared to the controls. (2.60±2.05 vs 1.74±0.70, p=0.001) Also, PLR was significantly increased in BRVOs compared to the controls. (129.70±68.77 vs 107.96±40.65, p=0.023)Conclusion: In our study we found that NLR and PLR were significantly increased in BRVOs than in controls.
Keywords: Neutrophil/lymphocyte ratio; platelet/lymphocyte ratio; brachial retinal vein occlusion, retinal vessels.